2003
DOI: 10.1267/ahc.36.439
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Calcitonin Suppresses Growth Fraction of Thyroid C Cells

Abstract: Calcitonin (CT) is a peptide hormone synthesized and secreted by the parafollicular (C) cells of the thyroid. Little is known about the mechanisms controlling proliferation of C cells by other humoral factors including CT, and there is no report that CT suppresses C cell proliferation. The effects of short-term administration of CT on C cell growth fraction were analyzed using BrdU and CT double immunohistochemical method in the rat thyroid. Continuous administration of 0.4 IU/kg and 40 IU/kg synthetic salmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In this study, we demonstrated that treatment of Orx rats with salmon CT further decreased the already reduced Vc and Vvc of thyroid C-cells, whereas serum CT was elevated due to Orx. This inhibitory effect of exogenous CT on rat thyroid C-cell function and proliferation was described earlier (Morimoto et al 1984;Mori et al 2003). Exogenous CT suppresses C-cell function probably by involving a negative feedback mechanism.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In this study, we demonstrated that treatment of Orx rats with salmon CT further decreased the already reduced Vc and Vvc of thyroid C-cells, whereas serum CT was elevated due to Orx. This inhibitory effect of exogenous CT on rat thyroid C-cell function and proliferation was described earlier (Morimoto et al 1984;Mori et al 2003). Exogenous CT suppresses C-cell function probably by involving a negative feedback mechanism.…”
Section: Discussionsupporting
confidence: 75%
“…The mRNA for CT receptors has been shown to be expressed in both tissue and cell lines of human medullary thyroid carcinoma (Frendo et al 1998a, b). Therefore, CT may act directly via its own receptors on C-cells (Mori et al 2003). Under our experimental conditions, CT treatment also affected the overall structure of rat thyroid glands.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…CT down-regulates serum levels of calcium, by suppressing bone resorption and calcium excretion from the kidney [5,10,18]. On the other hand, excessive CT induces negative feedback to C cell proliferation [15]. These direct and specific actions of CT on thyroid, bone and kidney have been confirmed by the presence of specific calcitonin receptors (CTR).…”
Section: Introductionmentioning
confidence: 99%